Inter-comparison of network measurements of non-methane organic compounds with model simulations. (December 2015) - Chen, Sheng-Po; Su, Yuan-Chang; Chiu, Ching-Jui; Lin, Ching-Ho; Chang, Julius S.; Chang, Chih-Chung; Wang, Jia-Lin
Abstract: Ambient levels of total non-methane organic carbons (NMOCs) at air quality stations (AQSs, called AQS NMOCs) are compared with the summed concentrations of 56 NMHCs obtained from the Photochemical Assessment Monitoring Stations (called total PAMS). For mutual validation of the two networks, the total PAMS were compared with the AQS NMOCs at four sites on the island of Taiwan for the period 2007–2012. The inter-comparison of total PAMS and AQS NMOCs has been discussed previously, which reported that the total PAMS accounted for approximately 30% of the AQS NMOCs on average (Chen et al., 2014b). In this study, both the observed total PAMS and AQS NMOCs were further compared with the emissions and model simulations for mutual validation. A three-dimensional Eulerian air quality model was used to simulate total PAMS and total VOCs, which were then inter-compared with the observed total PAMS and AQS NMOCs, respectively. We found closely agreeing results between the observed and simulated total PAMS, affirming that the treatment of meteorology and VOC emissions in the model was sufficiently robust. Further, although the modeled VOC data agreed with the AQS NMOC observations for the sites in urban settings, a significant discrepancy existed for the industrial sites, particularly at the concentration spikes. Such a discrepancy was presumably attributed to high emissions of OVOCs from industrial complexes compounded by the lower sensitivity of AQS measurements for OVOCs compared with hydrocarbons. Consequently, using AQS NMOCs to represent ambient VOC levels should be limited to environments where the amounts of OVOCs are relatively small relative to total VOCs. Highlights: Total PAMS species accounted for approximately 70% of the total ambient NMHCs. Total PAMS simulations agreed well with observations. AQS NMOCs tend to underestimate VOC levels due to lower sensitivity towards OVOCs.